The Effectiveness of Social Services in Handling Beggars as Social Welfare Service Needers in South Tangerang City - Abdul Rahman; Hanifa Arwanti Lubis; Syifa Astasia Utari (Jurnal Pemerintahan dan Kebijakan (JPK), 2023)
This study aims to analyze the effectiveness of Social Services in handling beggars as Social Welfare Service Needers (PPKS) in South Tangerang City since, until now, they still encounter many obstacles. First, handling PPKS has not become one of the government’s main agendas. Second, the problems are the rampant existence of beggars who disturb public order and cause public unrest. The third, based on a study by the Integrated Service Center Team for the Empowerment of Women and Children (P2TP2A) of South Tangerang City, is not optimal for handling beggars/PPKS in South Tangerang City. This study used a descriptive method with a qualitative approach. Meanwhile, the organizational effectiveness theory of Steers et al., which consists of 4 indicators of organizational effectiveness, such as organizational characteristics, environmental characteristics, worker characteristics, and management practices, became the main analytical knife of the study. This study concluded that the Social Services have not effectively handled beggars as Social Welfare Service Needers in South Tangerang City. Several aspects need to be improved, such as more intense training for employees of the South Tangerang City Social Service, additional human resources who have a background in social science studies, providing public complaint channels, conducting strict action against beggars who have been caught twice, gaining effectiveness counseling to rehabilitated beggars, developing social institutions, and formulating regional regulations governing sanctions for beggars.